Paeoniflorin Rescued MK-801-Induced Schizophrenia–Like Behaviors in Mice via Oxidative Stress Pathway - Liang, Jia-Quan; Chen, Xi; Cheng, Yong (Frontiers in Nutrition, 2022)
Schizophrenia (SCZ) affects approximately 1% population worldwide, and the first-line antipsychotics have partial reactivity or non-reactivity with side effects. Therefore, there is an urgent need to find more effective drugs. Paeoniflorin (PF) is the main effective component of traditional Chinese medicine from white peony, red peony and peony bark, which acts as a neuroprotective agent. The purpose of this study was to investigate whether PF can rescue MK-801 induced schizophrenia-like behavior in mice. Our results demonstrated that intragastric administration of PF ameliorated MK-801 induced schizophrenia–like behaviors in mice as demonstrated by prepulse inhibition of acoustic startle response, fear conditioning test for memory and open field test for activity. In contrast, the first-line antipsychotics-olanzapine reversed the prepulse inhibition deficits and hyperactivities, but not memory deficits, in the model mice. Further analysis showed that PF reduced oxidative stress in the MK-801-treated mice, as evidenced by the increased superoxide dismutase levels and decreased malondialdehyde levels in the blood of the model mice. In addition, PF treatment inhibited the expression of the apoptotic protein Bax and restored the expression of tyrosine hydroxylase in the brains of the model mice. in vitro data indicated that PF protected against oxidative stress induced neurotoxicity in the primary cultured hippocampal neurons. In conclusion, our results were the first to provide evidence that PF rescued schizophrenia-like behaviors (both positive symptoms and cognitive impairments) in rodents through oxidative stress pathway, and therefore provide a novel strategy for treatment of SCZ. However, more pre-clinical and clinical research are needed to translate the present findings into clinics for a treatment of schizophrenia.